Desenvolvimento do omaso de bovinos da raça Nelore (Bos taurus indicus) durante o período pré-natal - do Nascimento, Gabriela Mansano; Perri, Silvia Helena Venturoli [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Monteiro, Cristina Maria Rodrigues [UNESP] (My University, 2013)
The development of the stomach of domestic mammals is a complex process, especially in ruminants. The aim of this study was to analyze this organ during prenatal period. Omasum samples of Nelore fetuses (Bos taurus indicus) were divided into five groups of six samples each: 1- fetuses from 9 to 15 weeks (8 to 21cm) of gestation, 2 - fetuses from 16 to 22 weeks (23 to 37cm), 3 - fetuses from 23 to 29 weeks (40 to 58cm), 4 - fetuses from 30 to 36 weeks (61 to 77cm) and 5 - fetuses from 37 to 43 weeks (79 to 88cm). The histological sections were stained with Hematoxylin and Eosin and Picrossirius and examined by light microscopy. In fetuses of 11 cm it was observed mucosa with uniform primary, secondary and tertiary blades and all layers present. The fetus with 13.5 cm presented quaternary blades emergence, papillae on primary and secondary blades and formation of the muscularis mucosae. At 28 cm it were observed papillae in development, as well as the blades, especially the quaternary. In 42 cm fetuses was early epithelial keratinization and at 56 cm it was fully keratinized. In 60 cm fetuses the blades presented large papillae with tapered apex and at 65 cm there was decreased epithelium and increase of the muscle layer. In the fetus of 83 cm it were observed thin sections, discrete muscularis mucosa and papillae over the entire organ surface. It was concluded that the blades and papillae were structures that presented more changes during fetal development.
Development of the omasum of Nelore cattle (Bos taurus indicus) during the prenatal period
Keywords: Fetuses; Morphology; Pluricavitary Ventricle; Ruminants